2010
DOI: 10.1002/jsfa.3989
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrolyzed Chlorella vulgaris by malted barley on the immunomodulatory response in ICR mice and in Molt-4 cells

Abstract: These results indicate that hydrolyzed Chlorella vulgaris by malted barley is useful for immune function improvements, enhanced physical stamina, and as a candidate for an anti-fatigue or antidepressant agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…Reduction of the immobility time during forced swimming test traditionally interpreted as a measure of 'behavioral despair' or 'learned helplessness' (Gao et al, 2014). Many studies show the possibility that retrenchment the amount of time an animal spends immobile in the forced swimming test by natural compounds have the relation with cytokines and blood parameters (Shin et al, 2004;Kim et al, 2008;Kim et al, 2010) However, it was not illuminated yet detail mechanism on its relation between immobility time and change of cytokines/ blood parameters. The immobility time of mice in fluoxetine administrated groups, LF administrated groups, and betaine administrated groups reduced significantly at the last day, compared with saline administrated group (P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduction of the immobility time during forced swimming test traditionally interpreted as a measure of 'behavioral despair' or 'learned helplessness' (Gao et al, 2014). Many studies show the possibility that retrenchment the amount of time an animal spends immobile in the forced swimming test by natural compounds have the relation with cytokines and blood parameters (Shin et al, 2004;Kim et al, 2008;Kim et al, 2010) However, it was not illuminated yet detail mechanism on its relation between immobility time and change of cytokines/ blood parameters. The immobility time of mice in fluoxetine administrated groups, LF administrated groups, and betaine administrated groups reduced significantly at the last day, compared with saline administrated group (P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the reduction of BUN values by LF and betaine indicated that they could have a play in alleviating kidney injury by forced swimming test. Immunoregulatory cytokines play an important role in immune response (Bernabei et al, 2003;Kim et al, 2010). Of these immunoregulartory cytokines, they are known that IFN- produced by T and natural killer cells is considered the principal effector cytokine of cell-mediated immunity, and IL-2 is a T cell growth factor, can augment natural killer cell cytolytic activity, or promotes immunoglobulin production by B cells (Kim et al, 2006;Lenardo, 1991).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from its effect on water quality, the abundance of Chlorella in green water ponds might have helped to improve the shrimp's immune competence to resist disease thus resulting in higher survival (Ponprateep et al, 2011;Tendencia et al, 2012). It has been reported that hydrolysed Chlorella vulgaris promotes the release of interferons (IFN) in mice (Kim et al, 2010). Furthermore, IFNs have protective immuno-modulatory function against pneumonia virus in mice leading to high survival (Rigaux et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…클로렐라 내 함유되어 있는 CGF(chlorella growth factor)는 성장 촉진 물질로서, 항암효과 (Justo, 2001;Noda et al, 1996), 성인병 예방 효과 (Hasegawa et al, 1995) 및 골다공증의 예방에 효 과적인 것으로 보고된 바 있다 (Jung, 2003;Kim et al, 2003). Kim et al(2010) - Table 2에서 나타내었다. 실험 종료에 따른 육계 체중을 조사한 결과, 클로렐라 사 료첨가제 0.5%(T4) 및 1.0% 급여구(T3)에서 각각 1,670 g, 1,672 g 으로 대조구 및 다른 처리구와 비교 시 유의적으로 높게 나타났으며(P<0.05), 증체량 역시 클로렐라 사료첨가 제 급여 처리구(T3 및 T4)에서 유의적인 개선 효과를 나타 내었었다(P<0.05). 사료 섭취량 및 사료 요구율은 처리구간 Table 4.…”
unclassified